Testosterone Deficiency Increases Hospital Readmission and Mortality Rates in Male Patients with Heart Failure - Santos,Marcelo Rodrigues dos (2015)
Background:Testosterone deficiency in patients with heart failure (HF) is associated with decreased exercise capacity and mortality; however, its impact on hospital readmission rate is uncertain. Furthermore, the relationship between testosterone deficiency and sympathetic activation is unknown.Objective:We investigated the role of testosterone level on hospital readmission and mortality rates as well as sympathetic nerve activity in patients with HF.Methods:Total testosterone (TT) and free testosterone (FT) were measured in 110 hospitalized male patients with a left ventricular ejection fraction < 45% and New York Heart Association classification IV. The patients were placed into low testosterone (LT; n = 66) and normal testosterone (NT; n = 44) groups. Hypogonadism was defined as TT < 300 ng/dL and FT < 131 pmol/L. Muscle sympathetic nerve activity (MSNA) was recorded by microneurography in a subpopulation of 27 patients.Results:Length of hospital stay was longer in the LT group compared to in the NT group (37 ± 4 vs. 25 ± 4 days; p = 0.008). Similarly, the cumulative hazard of readmission within 1 year was greater in the LT group compared to in the NT group (44% vs. 22%, p = 0.001). In the single-predictor analysis, TT (hazard ratio [HR], 2.77; 95% confidence interval [CI], 1.58–4.85; p = 0.02) predicted hospital readmission within 90 days. In addition, TT (HR, 4.65; 95% CI, 2.67–8.10; p = 0.009) and readmission within 90 days (HR, 3.27; 95% CI, 1.23–8.69; p = 0.02) predicted increased mortality. Neurohumoral activation, as estimated by MSNA, was significantly higher in the LT group compared to in the NT group (65 ± 3 vs. 51 ± 4 bursts/100 heart beats; p < 0.001).Conclusion:These results support the concept that LT is an independent risk factor for hospital readmission within 90 days and increased mortality in patients with HF. Furthermore, increased MSNA was observed in patients with LT.